Erodibility and loss of marly drived soils - Reza Sokouti; Somaieh Razagi (Eurasian Journal of Soil Science, 2015)
Considering to high distribution of the marly lands in west Azerbaijan province and high sediment yield of such lands, in this research, the relation among the form and the rate of erosion on marls with their erodibility properties were studied. Therefore, marly regions of province with the special properties were recognized and the soils samples were taken from 15 points of the topsoil of this area. Soil erodibility indices were determined and analyzed by statistical methods considering the form and rate of erosion. Also portable rain simulator were used to study of the runoff and sediment yield potential of such soils. Finally the factors affected the soil erodibility were determined by variance analysis. Results showed erosion rate could be classified as moderate. Gully erosion had highest number in Gare-Agaj and Gare-tappe areas whereas rill erosion had high number in all area of marly lands. Surface runoff volume ranged between 255 to 577 cm3 in Shabanlu region and surface runoff coefficient varied from 0.23 to 0.53 in Gare-tappe. Maximum turbidity yield was determined 180 gr/lit in Gare-Agaj area. It was found that the clay ratio played the important role (P≤0.05) in creating the gully erosion and the volume of runoff in the surface and rill erosion.